KEMAMPUAN MENULIS TEKS PERSUASI OLEH SISWA KELAS VIII-5 SMP NEGERI 4 MEDAN TAHUN AJARAN 2019/2020 - Sarifah Hanum (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2021)
The results showed that the ability to write persuasive texts based on the aspect of issue recognition an average score of 71.7%, a series of arguments an average score of 74.16%, a statement of invitation an average score of 64.16%, reaffirmation an average score of 49 .6%, technical words score an average of 80.8%, and argumentative conjunctions score an average of 65.8%. So, the results show that grade VIII-5 students of SMP Negeri 4 Medan are categorized as sufficient in writing persuasive texts with the total average score of 66 and is in the sufficient category